Karakteristik Kayu Lapis Dari Bahan Baku Kayu Karet (Hevea braziliensis muell. Arg) Berdasarkan Umur Pohon - Fakhdian Setiawan; Rudianda Sulaeman; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT Product testing made reference to Standar Nasional Indonesia (SNI) 01-5008.2-1999 Plywood for Structural. Physical properties of plywood includeswater level of plywood withtree ages 20 yearswith average 14,43% ranged from 14,12% until14,67% andfor plywoodwith tree ages 25 yearswith average 14,60%  ranged from 14,31% until 14,91%. Plywood densitywith tree ages 20 yearswith average 0,63 g/cm3ranged from 0,62 g/cm3until 0,64 g/cm3and for plywoodwith tree ages 25 years with average 0,65 g/cm3ranged from 0,63 g/cm3until 0,66 g/cm3. Firmness an adhesive plywood withtree ages 20 yearswith average 9,25 kg/cm2ranged from 9,15 kg/cm2until 9,36 kg/cm2and for plywoodwith tree ages 25 yearswith average 9,98 kg/cm2ranged from 9,60 kg/cm2until 10,23 kg/cm2. Mechanical properties of plywood includesfirmness broken (Modulus of Rupture) ofplywood withtree ages 20 years with average 19,32 kg/cm2ranged from 18,00 kg/cm2 until 20,70 kg/cm2 and for plywoodwith tree ages 25 yearswith average 21,40 kg/cm2ranged from 18,72 kg/cm2 until 23,34 kg/cm2. Constancy of an arched (Modulus of Elasticity) plywoodwith tree ages 20 years with average 19,35 kg/cm2ranged from 18,11 kg/cm2until 20,65 kg/cm2and for plywoodwith tree ages 25 years with average 21,38 kg/cm2ranged from 18,70 kg/cm2until 23,33 kg/cm2. Keywords: Plywood, Physical properties, Mechanical properties